The relative age effect in Austrian youth ski racing - Müller, L.; Hildebrandt, C.; Ehn, G.; Müller, E.; Raschner, C. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
Thus, the aims of the present study were first to examine the RAE at the youngest levels of youth ski racing in Austria, and second, to investigate the influence of the relative age on the overall performance in youth ski racing.